Dangling dancers, vertebrae creak, Female suicide, and Greek tragedy (2021)
Based on Nicole Loraux’s Tragic Ways of Killing a Woman, this article aims to present very different ways in which the death of a man and the death of a woman are thought of in a Greek polis. It seeks to emphasize the way in which the death of women is dramatized in Greek tragedy, a literary genre considered as a place where the border lines between the two ways of dying fade, albeit ambiguously. Based on this, some features of political anthropology are shown in which the ancient Greek understanding supports the diverse meanings of death in the field of problems examined, in function of the sex of the person who is to die. Therefore, the objective is not to propose or carry out neither a study that suggests argumentative lines in favor of an understanding of the tragic, nor an interpretative study about the essence of that great artistic fruit of the Greek spirit.